Gamification and Behaviour Recognition in Literacy Assessments for Sub-Saharan African Communities - Marcos André Correia de Oliveira (2015)
Sub-Saharan African countries present the lowest adult and youth literacy rates in the world. Simultaneously, they have led the growth of mobile communications worldwide, mainly done by smartphones. In this sense, mobile devices can play a crucial role in monitoring the literacy of this African region. The purpose of this dissertation is to develop a mobile application to assess and monitor the degree of literacy of children and adults in sub-Saharan communities. In this context, the evaluation should be realized without the need to be performed by an individual specialized in the area, and using standardized and at the same time captivating tests. In order to keep the user committed and engaged to the process, it is intended to use gamification techniques. During the literacy assessment process, specific behaviours of the user interacting with the application may occur. Through these same behaviours, the application may identify and analyse the user profile, allowing the interface and usability aspects to be adjusted based on these aspects. Thus, this tool stands out from traditional literacy tests based on pen-and-paper. The solution consists, initially, in conducting a literature review that covers the different tools and literacy assessment tests, the human-computer interaction for African users with low literacy rates, as well as gamification techniques and adaptive interfaces on mobile devices. The application will be developed according to an iterative process of user-centred design. Thus, after defining an initial strategy, iterations are expected through the processes of analysis and requirements specification, conceptual design and evaluation, until a final result is obtained. Due to geographical constraints, three first sessions of tests were conducted in Portugal, participating users aged between seven and twelve years old, having distinct levels of knowledge of the English language and different types of contact with mobile devices. The results show the efficacy of gamifying literacy in order to provide a captivating experience to the users and promising results about the adaptive interface. It is expected that this tool will help improve the literacy rate in sub-Saharan Africa, enabling teachers and volunteers to diagnose and easily monitor the degree of literacy in these regions. It is also expected that it will stimulate the spirit of mutual help among community members, therefore, combating low level literacy in their home areas. Keywords: literacy assessment systems, gamification of literacy, user behaviour recognition, user-centred design, adaptive interfaces, sub-Saharan Africa communities